An entire exon 3 germ-line rearrangement in the BRCA2 gene: pathogenic relevance of exon 3 deletion in breast cancer predisposition - Demange Liliane; Limacher Jean; Noguès Catherine; Caron Olivier; Bièche Ivan; Lefol Cédrick; Caputo Sandrine; Schultz Inès; Rouleau Etienne; Muller Danièle; Lidereau Rosette; Fricker Jean; et al. (BMC, 2011)
Abstract Background Germ-line mutations in the BRCA1 and BRCA2 genes are major contributors to hereditary breast/ovarian cancer. Large rearrangements are less frequent in the BRCA2 gene than in BRCA1. We report, here, the first total deletion of exon 3 in the BRCA2 gene that was detected during screening of 2058 index cases from breast/ovarian cancer families for BRCA2 large rearrangements. Deletion of exon 3, which is in phase, does not alter the reading frame. Low levels of alternative transcripts lacking exon 3 (Δ3 delta3 transcript) have been reported in normal tissues, which raises the question whether deletion of exon 3 is pathogenic. Methods Large BRCA2 rearrangements were analysed by QMPSF (Quantitative Multiplex PCR of Short Fluorescent Fragments) or MLPA (Multiplex Ligation-Dependent Probe Amplification). The exon 3 deletion was characterized with a "zoom-in" dedicated CGH array to the BRCA2 gene and sequencing. To determine the effect of exon 3 deletion and assess its pathogenic effect, three methods of transcript quantification were used: fragment analysis of FAM-labelled PCR products, specific allelic expression using an intron 2 polymorphism and competitive quantitative RT-PCR. Results Large rearrangements of BRCA2 were detected in six index cases out of 2058 tested (3% of all deleterious BRCA2 mutations). This study reports the first large rearrangement of the BRCA2 gene that includes all of exon 3 and leads to an in frame deletion of exon 3 at the transcriptional level. Thirty five variants in exon 3 and junction regions of BRCA2 are also reported, that contribute to the interpretation of the pathogenicity of the deletion. The quantitative approaches showed that there are three classes of delta3 BRCA2 transcripts (low, moderate and exclusive). Exclusive expression of the delta3 transcript by the mutant allele and segregation data provide evidence for a causal effect of the exon 3 deletion. Conclusion This paper highlights that large rearrangements and total deletion of exon 3 in the BRCA2 gene could contribute to hereditary breast and/or ovarian cancer. In addition, our findings suggest that, to interpret the pathogenic effect of any variants of exon 3, both accurate transcript quantification and co-segregation analysis are required.